Analysis of the Impact of Covid-19 on the Tourism Sector - Cucu Hodijah; Rika Solihah; Rizky Ferrari Octavian (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
In the last decade, all countries have been shocked by the emergence of the COVID-19 pandemic which has had a crucial impact in all aspects so that various policies have been implemented, one of which is the social restriction system. Since the outbreak of covid-19, the Tourism Industry has also experienced paralysis, where all tourist destinations must be temporarily closed for an unpredictable time, to anticipate the transmission of the coronavirus or covid-19, especially since the enactment of the PSBB, various tourist attractions in Indonesia have been closed. The purpose of this study was to analyze the impact of the Covid-19 pandemic on the special tourism sector in Farmhouse tourism objects. This research method uses descriptive analysis, where primary data is obtained directly based on the results of interviews and observations at tourist objects. Meanwhile, secondary data is obtained through notes and publications as well as literature studies. The results showed that Covid-19 had an impact on the tourism sector, especially on Farmhouse tourism objects, this was indicated by a decrease in the number of tourist visits which decreased 80% during weekdays and 60% during weekends compared to the previous year.;